Effect of aqueous extract of Dicranopteris linearis leaves against paracetamol and carbon tetrachloride-induced liver toxicity in rats - Ismail, Noor Aisyah; Shamsahal Din, Nor Syafawati; Mamat, Siti Syariah; Zabidi, Zalina; Wan Zainulddin, Wan Noraziemah; Kamisan, Farah Hidayah; Yahya, Farhana; Mohtarrudin, Norhafizah; Mohd Desa, Mohd Nasir; Zakaria, Zainul Amiruddin (Faculty of Pharmacy, University of Karachi, 2014)
The present study aimed to determine the hepatoprotective activity of Dicranopteris linearis L. (family Gleicheniaceae) leaf aqueous extract (DLAE) using two models of liver injury in rats. Rats were divided into ten groups (n=6) and received dH2O (negative control), 200 mg/kg silymarin (positive control) or DLAE (50, 250 and 500 mg/kg) orally once daily for 7 consecutive days and on the 8th day subjected to the hepatotoxic induction either using carbon tetrachloride (CCl4) or paracetamol (PCM). The bloods and livers were collected and subjected to biochemical and microscopical analysis. From the data obtained, only the highest dose of DLAE significantly (p<0.05) reduced the ALP, ALT and AST levels in CCl4-and PCM-induced hepatotoxic rats while the other doses caused significant (p<0.05) reduction only in the levels of ALT and AST. The histological results obtained were in line with the biochemical analysis wherein reduction in the CCl4- and PCM-induced tissue formation of necrosis, steatosis and inflammation occurred in a dose-dependent manner. In conclusion, the DLAE possesses hepatoprotective activity, which could be attributed to its free radicals scavenging and antioxidant activities, and high flavonoids content. Thus, in-depth studies regarding the hepatoprotective activity of DLAE are warranted.